2019
DOI: 10.17060/ijodaep.2019.n1.v3.1529
|View full text |Cite
|
Sign up to set email alerts
|

Creatividad y tecnologías emergentes en educación

Abstract: La creatividad es un valor en alza debido a su estrecha relación con la solución de problemas y el emprendimiento. Es conveniente que esta creatividad sea fomentada desde los primeros años de escolarización cuando el mundo de fantasía y simbólico del niño está en plena ebullición y dónde todo es posible. Así, el fomento de la creatividad, aparece convenientemente contemplado en el currículum de la etapa. Por otro lado, desde las administraciones educativas se está promoviendo el uso de metodologías didácticas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 6 publications
0
3
0
6
Order By: Relevance
“…As a conclusion, our study has shown that creativity and life satisfaction can be improved in university classrooms with intervention programs such as ours, taking into account that they are competencies demanded by companies ( Bouchard, 2014 ) and that they can have a decisive character for achievement ( Fernández-Berrocal and Ruiz Aranda, 2008 ; Figueiredo-Ferraz et al, 2009 ; Anwar et al, 2012 ; Belmonte, 2013 ; Saremi and Bahdori, 2015 ; Bernabé et al, 2017 ; Peña García et al, 2017 ) and, as we pointed out, to improve the employability of our students, productivity, and quality of work ( Diener and Biswas-Diener, 2002 ; del Águila Ríos et al, 2019 ) and the capacity for innovation that today’s society demands of us ( European Commission, 2008 ), in agreement with the improvement guidelines of the Bologna plan, included in the Europe 2030 strategy ( Sánchez Ruiz, 2020 ). The review by Gilar-Corbi et al (2018) , attests to the growing interest in recent years of teaching these contents and intentions to our higher education students.…”
Section: Discussionmentioning
confidence: 99%
“…As a conclusion, our study has shown that creativity and life satisfaction can be improved in university classrooms with intervention programs such as ours, taking into account that they are competencies demanded by companies ( Bouchard, 2014 ) and that they can have a decisive character for achievement ( Fernández-Berrocal and Ruiz Aranda, 2008 ; Figueiredo-Ferraz et al, 2009 ; Anwar et al, 2012 ; Belmonte, 2013 ; Saremi and Bahdori, 2015 ; Bernabé et al, 2017 ; Peña García et al, 2017 ) and, as we pointed out, to improve the employability of our students, productivity, and quality of work ( Diener and Biswas-Diener, 2002 ; del Águila Ríos et al, 2019 ) and the capacity for innovation that today’s society demands of us ( European Commission, 2008 ), in agreement with the improvement guidelines of the Bologna plan, included in the Europe 2030 strategy ( Sánchez Ruiz, 2020 ). The review by Gilar-Corbi et al (2018) , attests to the growing interest in recent years of teaching these contents and intentions to our higher education students.…”
Section: Discussionmentioning
confidence: 99%
“…Que favorece el trabajo colaborativo entre docentes y estudiantes que utilizan herramientas informáticas para un mejor estudio. En ese sentido, se habla de las pedagogías y tecnologías emergentes como medios para diversificar y fortalecer el proceso enseñanza-aprendizaje para asegurar el logro de los objetivos educativos propuestos, y de esta forma, evitar o disminuir los índices de deserción de los estudiantes (Aparicio y Ostos, 2021;Del Águila et al, 2019;Lengua et al, 2020). En la medida en que los docentes puedan transmitir de diversas formas y con un enfoque innovador los saberes que necesita el estudiante para lograr un buen desempeño, este desarrolla sus habilidades cognitivas, digitales y sociales que le permitan adquirir los conocimientos propios de su disciplina, y responder a las necesidades de su entorno.…”
Section: Tecnologías Educativas Que Fortalecen El Proceso De Enseñanz...unclassified
“…Creativity is having ideas and communicating them; When relating it to education, it is indicated that it is a social value and not only a psychological scientific one (Galvis, 2017;Márquez & Gaeta, 2017;Mora et al, 2018). For this, it is necessary to train teachers in this area, taking into account new technologies (Del Águila et al, 2019;Nella, 2020;Oliva & Flores, 2015).…”
Section: Ketty Aragundi; Cinthya Game-varamentioning
confidence: 99%